Classic and Contemporary Mudharabah Philosophy between Theoretical and Practice - Muhammad Yunus; Mugni Muhit (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
Islam as a religion of rahmatan lil'alamin pays great attention to human activities in muamalah, as well as in business matters. The cooperation system or often referred to as a participation contract in business (Mudharabah) is something that can be applied. The parties to this agreement are the fund manager (mudharib) and the fund owner (shohibul maal). However, along with the development of the times and the diverse business needs that require optimum capital, this kind of cooperation model has also undergone an evolution. Where in the initial concept there were only two unionized parties, in the current concept a third party is needed, namely Islamic financial institutions and the like. The goal of this study is to determine how mudharabah contracts are described in traditional fiqh texts and how LKS goods relate to mudharabah contracts.